Impact of the 2018 Society of Critical Care Medicine Pain, Agitation/Sedation, Delirium, Immobility, and Sleep Guidelines on Nonopioid Analgesic Use and Related Outcomes in Critically Ill Adults After Major Surgery. (26th October 2021) - Sutton, Spencer; McCrobie, Trevor R.; Kovacevic, Mary R.; Dube, Kevin M.; Szumita, Paul M.; Herod, Kyle; Bezio, Aaron; Choi, Hannah; Duprey, Matthew S.; Zeballos, Jose; Devlin, John W.
Abstract : We compared ICU nonopioid analgesic use, opioid use, and pain before and after Pain, Agitation/Sedation, Delirium, Immobility, and Sleep guideline publication at one academic center among critically ill adults receiving an opioid infusion and greater than or equal to 24 hours of mechanical ventilation after major surgery. The 2017 ( n = 77) and 2019 ( n = 57) groups were similar at baseline. The 2019 (vs 2017) patients were more likely to receive scheduled IV/oral acetaminophen (84% vs 69%; p = 0.05), less likely to receive a lidocaine patch (33% vs 50%; p = 0.05), and just as likely to receive ketamine (4% vs 3%; p = 1.0), an nonsteroidal anti-inflammatory drug (7% vs 3%; p = 0.26), or gabapentin/pregabalin (16% vs 9%; p = 0.23). Daily average opioid exposure (in IV morphine milligram equivalent) was not different (70 [42–99] [2017] vs 78 mg [49–109 mg]; p = 0.94). The 2019 (vs 2017) group spent more ICU days with severe pain ( p = 0.04). At our center, Pain, Agitation/Sedation, Delirium, Immobility, and Sleep guideline publication had little effect on nonopioid analgesic or opioid prescribing practices in critically ill surgical adults.